Analisis Rasio Keuangan untuk Menilai Kinerja PT Siantar Top Tbk Periode 2020-2023 - Bintang, Krista Dini Ofiana (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to evaluate the financial performance of PT Siantar Top Tbk during the 2020-2022 period using financial ratio analysis. The object of this research is the company's financial statements, which include the income statement, balance sheet, and cash flow. Samples are taken from financial reports that have been officially published. Data was collected through the documentation method and analyzed descriptively and quantitatively by calculating liquidity, solvency, and profitability ratios. The results showed strengths and weaknesses in the company's financial performance, especially in the aspects of operational efficiency and leverage strategy. This study recommends more strategic financial management to support sustainable growth.